2000
DOI: 10.4049/jimmunol.164.11.6075
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional Resistance of Human H2 Glioblastoma Cells to Complement-Mediated Killing by Expression and Utilization of Factor H and Factor H-Like Protein 1

Abstract: Of over 20 nucleated cell lines we have examined to date, human H2 glioblastoma cells have turned out to be the most resistant to complement-mediated cytolysis in vitro. H2 cells expressed strongly the membrane attack complex inhibitor protectin (CD59), moderately CD46 (membrane cofactor protein) and CD55 (decay-accelerating factor), but no CD35 (complement receptor 1). When treated with a polyclonal anti-H2 Ab, anti-CD59 mAb, and normal human serum, only 5% of H2 cells became killed. Under the same conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
97
1
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(100 citation statements)
references
References 45 publications
0
97
1
2
Order By: Relevance
“…14 Cancer cells were reported to either overexpress fH or bind fH on their surface to evade complement-mediated tumor killing. 15 A clinical study showed that a polymorphism in the fH gene is associated with event free survival after rituximab treatment in FL patients, although the study had relatively low power and this finding should be confirmed. 16 The same study also found associations in CFHR1 and CFHR5, genes that are located near to CFH and encode fH-related proteins.…”
Section: Soluble Complement Regulatorsmentioning
confidence: 97%
“…14 Cancer cells were reported to either overexpress fH or bind fH on their surface to evade complement-mediated tumor killing. 15 A clinical study showed that a polymorphism in the fH gene is associated with event free survival after rituximab treatment in FL patients, although the study had relatively low power and this finding should be confirmed. 16 The same study also found associations in CFHR1 and CFHR5, genes that are located near to CFH and encode fH-related proteins.…”
Section: Soluble Complement Regulatorsmentioning
confidence: 97%
“…Trypanosomes are able to activate the alternative complement pathway in blood (35), whereas decreased complement activation was reported during the 1980s in infective cultures of T. cruzi, responsible for Chagas' disease (36). Complement factor H is the principal inhibitor of the alternative pathway, and is also involved in the protection of epithelial, endothelial, and some cancer cells against complement action (37). In our population of T. b. gambiense patients, overexpression of CFH during the second stage of disease was only confirmed with ELISA.…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing analysis showed that the 52 clones represented 30 distinct antigens (Table 1). Of these 30 antigens, one is the CT antigen CAGE protein, and the other 13 antigens, which had previously been reported to be involved in tumorigenesis or suspected to be involved in tumour progression, including CDC37 (Stepanova et al, 2000), MIF (Li et al, 2004), galectin 4 (Huflejt and Leffler, 2004), galectin 8 (Bidon-Wagner and Le Pennec, 2004), PINCH (WangRodriguez et al, 2002), SPRY2 (Lee et al, 2004a), HSPCA (Becker et al, 2004;Huang et al, 2004b), transgelin 2 (Shields et al, 2002), HDAC2 , H factor (Junnikkala et al, 2000), AAT (Huang et al, 2004a), B factor (Perou et al, 1999), PIBF (Lachmann et al, 2004). Three other antigens (SR140 protein, SFRS2IP, RNPC2) may be involved in the regulation of alternative mRNA splicing, PSMA7 is related to hepatitis B and hepatitis C viral replication (Zhang et al, 2000;Kruger et al, 2001), and the remaining 12 antigens have no known association with cancer or hepatitis B or hepatitis C.…”
Section: Serex Defined Hcc-associated Antigensmentioning
confidence: 99%